2019
DOI: 10.1002/ejoc.201901142
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of LacNAcLex‐ and DimLex‐BSA Conjugates and Binding to Anti‐Polymeric Lex mAbs

Abstract: The chemical synthesis of tetra‐ and pentasaccharide fragments of the tumor‐associated carbohydrate antigen dimeric Lewis X (dimLex) lacking either both or only the non‐reducing end fucosyl residues is described following a 1 + 1 + 1 synthetic strategy. Use of a 6‐chlorohexyl aglycon gave access to hexyl glycoside soluble inhibitors as well as the 6‐aminohexyl glycoside pentasaccharide. The 6‐aminohexyl glycoside pentasaccharide and a dimLex analogue were conjugated to BSA via a squarate linker and the glycoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
(34 reference statements)
1
3
0
Order By: Relevance
“…In turn, the five azidononyl oligosaccharide glycosides were submitted to one-step global deprotection in dissolving metal conditions to yield the final deprotected tri- to pentasaccharides aminononyl glycosides 3 , 4 , 6 , and 10 . As we have previously observed, the deprotection of the azidononyl pentasaccharide 56 also gave a non-negligible amount (16%) of the nonyl pentasaccharide 9 . The nonyl glycosides 5 and 7 were obtained, following full deprotection/reduction of protected chlorononyl analogues under dissolving metal conditions.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In turn, the five azidononyl oligosaccharide glycosides were submitted to one-step global deprotection in dissolving metal conditions to yield the final deprotected tri- to pentasaccharides aminononyl glycosides 3 , 4 , 6 , and 10 . As we have previously observed, the deprotection of the azidononyl pentasaccharide 56 also gave a non-negligible amount (16%) of the nonyl pentasaccharide 9 . The nonyl glycosides 5 and 7 were obtained, following full deprotection/reduction of protected chlorononyl analogues under dissolving metal conditions.…”
Section: Discussionsupporting
confidence: 79%
“…The structure of this pentasaccharide was confirmed in 1 H NMR, which showed a triplet at 0.86 ppm that correlated in the HSQC with a methyl group carbon at 16.3 ppm. While the reduction of a chloroalkyl glycoside in dissolving metal conditions is expected to lead to the corresponding alkyl glycoside, 40 this is the second instance 38 during which we observe the loss of an azido group from an azidoalkyl glycoside and the formation of the corresponding alkyl glycoside in non-negligible amount while reducing an azidoalkyl glycoside oligosaccharide. Furthermore, we observed that nonyl glycoside tetrasaccharide 9 had reduced solubility in water.…”
Section: ■ Results and Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…We have previously reported the chemical synthesis of the DimLe x propyl hexasaccharide 6 as well as that of the Le x methyl glycoside 7 [ 38 , 43 ]. In addition, we have also described the synthesis of tri-, tetra-, and pentasaccharide fragments of DimLe x 8 , 10 – 14 [ 44 , 45 , 46 , 47 ] shown in Figure 3 . Tetrasaccharide fragment 9 (Lex[1,3]Gal, Figure 3 ) was a generous gift of Samain and co. [ 48 ].…”
Section: Resultsmentioning
confidence: 99%